2020
DOI: 10.1111/jfb.14412
|View full text |Cite
|
Sign up to set email alerts
|

Effects of biological traits on capture‐induced parturition in a freshwater stingray and perspectives for species management

Abstract: Elasmobranchs are particularly vulnerable to overexploitation and population depletion, especially due to their life-history traits, such as low reproductive output and slow growth. Given that capture-induced parturition (abortion or premature birth) is a common consequence of fisheries in elasmobranchs, but still little studied, we

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…T. dumerilii litter size ranges from two to five pups (Marshall et al, 2007), so the presence of four or more pups indicated that potentially two females gave birth the same night. The identification of the female(s) that gave birth was initially based on visual inspection of females' body appearance because near-term pregnancy is evident from dorsal bulges on the two sides, which disappear immediately after parturition (de Sousa Rangel et al, 2020). To confirm parturition, females suspected to have given birth were dip-netted, drawn to the side of the housing tank, and, while lightly restrained, checked with the ultrasound.…”
Section: Neonates' Morphological Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…T. dumerilii litter size ranges from two to five pups (Marshall et al, 2007), so the presence of four or more pups indicated that potentially two females gave birth the same night. The identification of the female(s) that gave birth was initially based on visual inspection of females' body appearance because near-term pregnancy is evident from dorsal bulges on the two sides, which disappear immediately after parturition (de Sousa Rangel et al, 2020). To confirm parturition, females suspected to have given birth were dip-netted, drawn to the side of the housing tank, and, while lightly restrained, checked with the ultrasound.…”
Section: Neonates' Morphological Measurementsmentioning
confidence: 99%
“…In teleost fishes, stressors can affect a large variety of reproductive traits, both in parents, including reproductive hormone concentrations, reproductive behavior, vitellogenesis, gamete quality, fecundity, and ovulation timing, and in offspring born from stressed parents, such as behavior, hatching success, size, growth, swimming performance, feeding ability, and survival (Schreck et al, 2001;Milla et al, 2009;Leatherland et al, 2010;Schreck, 2010;Li and Leatherland, 2012;Pankhurst, 2016;Sopinka et al, 2016a). Few data exist for chondrichthyans and almost entirely concern observations of capture-induced premature parturition and abortion (Adams et al, 2018;Wosnick et al, 2019;de Sousa Rangel et al, 2020). Given the low probability of neonates surviving after premature parturition (Charvet-Almeida et al, 2005;Campbell et al, 2018), this is the most severe outcome representing the likely complete failure of the reproductive event.…”
Section: Introductionmentioning
confidence: 99%
“…tribute to two other factors that affect the populations of elasmobranchs, even when the fishes are released into the water: (a) a reduction in the number of spontaneous abortions, which occur due to the capture stress of females in advanced stages of gestation (Adams et al, 2018;Rangel et al, 2020) and (b) a reduction in the number of nest losses with ovigerous capsules, caused by the action of trawls (Cordeiro & Oddone, 2019;Rolim & Avila da Silva, 2016). In both cases, specimens may die or be born outside the parturition areas, decreasing the potential for success of these individuals (Adams et al, 2018).…”
mentioning
confidence: 99%
“…Parturition events were disclosed by the presence of neonates in the housing tanks. Identification of individual mothers was made by visual inspection of females' body appearance, because near‐term pregnancy is characterized by an evident bulge of the dorsal side of a female's body, which disappears immediately after parturition (Sousa Rangel et al, 2020). Parturition was then confirmed with ultrasound.…”
Section: Methodsmentioning
confidence: 99%